Renal oncocytoma in a cat with chronic renal failure. Issue 1 (February 2017) - Lee, Sora; Choi, Hyun-Ji; Lee, Han-Byul; Jo, Sung-Min; Mun, Ji-hye; Son, Woo-Chan
Case summary: A 9-year-old male neutered domestic shorthair cat presented with anorexia. Ultrasonography showed an irregularly shaped hypoechoic mass in the cranial pole of the right kidney. Ultrasound-guided fine-needle aspiration of the renal mass was performed. Cytology revealed moderate cellularity smears composed of epithelial cell clusters, which consisted of an exclusive population of oncocytic cells seen in sheets and papillary clusters along with abundant single cells. A moderate-to-abundant amount of densely stained granular cytoplasm with round nuclei and indistinct nucleoli was seen. The cytological diagnosis was renal oncocytic neoplasm. CT and surgical resection revealed a firm tan mass in the right kidney. A final diagnosis of renal oncocytoma was made on the basis of histology, immunohistochemical staining profile (positive for cytokeratin, and negative for chromogranin A, neuron-specific enolase and vimentin) of neoplastic cells, together with the electronic microscopy results. Relevance and novel information: We believe that this is the first report of the cytological features of feline renal oncocytoma.